2009
DOI: 10.1121/1.3058638
|View full text |Cite
|
Sign up to set email alerts
|

Perceptual recalibration of speech sounds following speech motor learning

Abstract: The functional sensorimotor nature of speech production has been demonstrated in studies examining speech adaptation to auditory and/or somatosensory feedback manipulations. These studies have focused primarily on flexible motor processes to explain their findings, without considering modifications to sensory representations resulting from the adaptation process. The present study explores whether the perceptual representation of the /s-b/ contrast may be adjusted following the alteration of auditory feedback … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

16
178
1

Year Published

2013
2013
2021
2021

Publication Types

Select...
4
2

Relationship

1
5

Authors

Journals

citations
Cited by 158 publications
(200 citation statements)
references
References 56 publications
(97 reference statements)
16
178
1
Order By: Relevance
“…Furthermore, the direction of the observed effects suggests that the change in perceptual function corresponds to motoric changes rather than auditory feedback. Previous experiments have found that passive exposure to the recorded speech of a participant compensating in response to AAF fails to change perceptual function, regardless of whether the recorded speech is made by an average compensating speaker (Shiller et al, 2009) or consists of a random selection of stimuli take from several compensating speakers (Lametti et al, 2014b). However, these experiments differed from the present study in that they did not examine how passive listening to such stimuli may affect CFC.…”
Section: Methodscontrasting
confidence: 52%
See 4 more Smart Citations
“…Furthermore, the direction of the observed effects suggests that the change in perceptual function corresponds to motoric changes rather than auditory feedback. Previous experiments have found that passive exposure to the recorded speech of a participant compensating in response to AAF fails to change perceptual function, regardless of whether the recorded speech is made by an average compensating speaker (Shiller et al, 2009) or consists of a random selection of stimuli take from several compensating speakers (Lametti et al, 2014b). However, these experiments differed from the present study in that they did not examine how passive listening to such stimuli may affect CFC.…”
Section: Methodscontrasting
confidence: 52%
“…As in other experiments (Shiller et al, 2009;Lametti et al, 2014b), no within-session significant correlations were found between production (standardized F2) and perception (centered response). The results seem to suggest that the effect of the altered feedback on perception only emerges when considering the differences in production and identification across the two sessions.…”
Section: Interactions Between Production and Identificationmentioning
confidence: 64%
See 3 more Smart Citations